Nutritional status and body composition in individuals with overweight or obesity using usual and unusual indicators (Research, Society and Development, 2021)
Objective: the aim of this study is to explore the nutritional status in adults according to usual and non-usual components of body composition. Methods: this is a descriptive study involving a sample of 274 Brazilians adults from the south of the country. The participants had their body composition assessed by an octapolar bioimpedanciometer (InBody 520 - Biospace) and the anthropometric parameters according to the WHO standard. The data was analyzed by the descriptive and inferential statistic with the software SPSS version 22.0. Results: The participants were grouped by nutritional status and sex. There were statistical differences between the groups (both nutritional status and sex) in all the variables, except age and stature. The correlation among the variables were also significant, except for the Lean Body Mass and Body Fat Percentage (LBM vs BFP) and for the Lean-to-Fat-Ratio and Lean Body Mass (LFR vs LBM). Final considerations: The results has shown that the usual and the non-usual parameters of body composition are related (most of them) and were more strongly related in the female group.